Prevalence of sexually transmitted infections in women of the Czech Republic Armed Forces: a cross-sectional pilot study - Karasek, Lubos; Smetana, J; Svobodova, P; Smahelova, J; Tachezy, R; Kiss, I; Nejedla, D (BMJ military health, 2025)
INTRODUCTION: Sexually transmitted infections (STIs) are an everlasting health issue globally. The military environment is recognised as a high-risk setting. Human papillomavirus (HPV), Chlamydia trachomatis and Neisseria gonorrhoeae are the most frequent STIs worldwide. This prospective cross-sectional pilot study focuses on the prevalence of selected STIs in the female population of the Czech Republic's Armed Forces. METHODS: C. trachomatis, N. gonorrhoeae and HPV detection and genotyping were performed between August 2020 and December 2022 in 141 women. Participants were divided into three groups according to their military status-recruits (n=72), active soldiers (n=25) and control civilian group (n=44). Cervical smear tests were performed, and data on STI risk factors were obtained through a questionnaire. RESULTS: A significant difference in the HPV prevalence between recruits (64.5 %) and both active soldiers (46.4 %) and civilians (47.3 %) was found when adjusted for age (p=0.007 and p=0.01, respectively). Lower age of coitarche (median 16; p=0.005) and smaller agglomeration origin (p=0.013) were reported for military recruits. No difference was proven in other researched risk factors. Associations between HPV detection and the higher number of sexual partners (p=0.013), early coitarche (p=0.016) and single marital status (p=0.002) across the groups were observed. Not a single case of N. gonorrhoeae was detected in any of the 141 participants. The prevalence of C. trachomatis did not differ significantly between the three evaluated groups-recruits, control civilian group, and active soldiers (5.6%, 2.3%, 0%, respectively; p=0.567). CONCLUSIONS: This pilot study showed a significantly higher HPV prevalence in female military recruits compared with both active military and civilian women. Recruits reported earlier coitarche which is a strong STI risk factor. Further study is needed to expand on the findings of this pilot study and generate data to support adjustment of STI preventive measures within the Czech Republic Armed Forces.
Keywords: Cross-Sectional Studies; Prevalence; Česká republika; průzkumy a dotazníky; prevalence; ozbrojené síly; průřezové studie; Military Personnel; Adult; Prospective Studies; Infectious diseases & infestations; Czech Republic; Infection control; ženské pohlaví; Humans; prospektivní studie; VIROLOGY; Surveys and Questionnaires; pilotní projekty; Pilot Projects; rizikové faktory; sexuálně přenosné nemoci; dospělí; Female; Risk Factors; Epidemiology; lidé; EPIDEMIOLOGY; Sexually Transmitted Diseases